The blue parakeet : rethinking how you read the Bible - McKnight, Scot (Grand Rapids, MI. Zondervan, 2018)
The Blue Parakeet is author Scot McKnight's compelling statement of how to read the Bible in a new evangelical generation. In reexamining the Bible, McKnight provides an exciting "New Way" that appeals to the millions in today's church who long to be authentic Christians but don't consider themselves theologically conservative or liberal.
The book and I -- The birds and I -- Inkblots and puzzles -- It's a story with power! -- The plot of the wiki-stories -- From paper to person -- God speaks, we listen -- The boring chapter (on missional listening) -- The year of living Jesus-ly -- Finding the pattern of discernment -- Slaves in the King and His Kingdom redemption story -- Atonement in the King and His Kingdom redemption story -- Justice in the King and His Kingdom redemption story -- The Bible and women -- What did women do in the Old Testament? -- What did women do in the New Testament? -- Silencing the blue parakeet (1) -- Silencing the blue parakeet (2) -- Now what? -- Appendix 1. A discernment quiz -- Appendix 2. Images of Jesus -- Appendix 3. 1 Corinthians 14:34-35 -- Appendix 4. Petronius on the new Roman woman -- Appendix 5. Juvenal on first-century woman -- Appendix 6. Junia is not alone -- Appendix 7. Genesis and science.
Includes bibliographical references.
Keywords: Bible -- Hermeneutics; Bible -- Criticism, Narrative